Deficiency of Ku Induces Host Cell Exploitation in Human Cancer Cells - Saydam, Okay; Saydam, Nurten (Frontiers in Cell and Developmental Biology, 2021)
Cancer metastasis is the major cause of death from cancer (Massague and Obenauf 2016; Steeg 2016). The extensive genetic heterogeneity and cellular plasticity of metastatic tumors set a prime barrier for the current cancer treatment protocols (Boumahdi and de Sauvage 2020). In addition, acquired therapy resistance has become an insurmountable obstacle that abolishes the beneficial effects of numerous anti-cancer regimens (De Angelis, Francescangeli et al. 2019; Boumahdi and de Sauvage 2020). Here we report that deficiency of Ku leads to the exploitation of host cells in human cancer cell line models. We found that, upon conditional deletion of XRCC6 that codes for Ku70, HCT116 human colorectal cancer cells gain a parasitic lifestyle that is characterized by the continuous cycle of host cell exploitation. We also found that DAOY cells, a human medulloblastoma cell line, innately lack nuclear Ku70/Ku86 proteins and utilize the host-cell invasion/departure mechanism for maintenance of their survival, similarly to the Ku70 conditionally-null HCT116 cells. Our study demonstrates that a functional loss of Ku protein promotes an adaptive, opportunistic switch to a parasitic lifestyle in human cancer cells, providing evidence for a previously unknown mechanism of cell survival in response to severe genomic stress. We anticipate that our study will bring a new perspective for understanding the mechanisms of cancer cell evolution, leading to a shift in the current concepts of cancer therapy protocols directed to the prevention of cancer metastasis and therapy resistance.